Praktik Pembelajaran Menulis oleh Guru Sekolah Dasar Muhammadiyah Berdasarkan Kurikulum Merdeka: Sebuah Studi Berdasarkan Data Wawancara: Praktik Pembelajaran Menulis oleh Guru Sekolah Dasar Muhammadiyah Berdasarkan Kurikulum Merdeka: Sebuah Studi Berdasarkan Data Wawancara - Rike Meyla Eka Saputri (Universitas Muhammadiyah Muara Bungo, 2025)
This study examined the practices of primary school teachers in Muhammadhya when teaching English letters as part of the free curriculum. Using a descriptive qualitative case study approach, researchers collected data via semi-structured interviews. The results show that teachers use student-centered and constructivist-based strategies, such as canva games, videos, and dialogues, supporting vocabulary development and trust writing. The study shows that the principles of independent curriculum as learning, which is an engaging and autonomous student in a religious school environment, through creative and adaptive education, is an engaging and autonomous student. This knowledge provides educators and political decisions. Makers provide useful insights aimed at improving writing in EFL primary school classrooms. Keywords: writing instruction, Kurikulum Merdeka, Muhammadiyah elementary school